The nurses’ perception of the factors influencing professional misconduct: A qualitative study - Ghobadi, Akram (Nursing ethics, 2024)
BackgroundProfessional misconduct undermines safe and quality care; however, little is known about its nature and influential factors.AimThis study aimed to explain the factors influencing professional misconduct in nurses.Research DesignThis qualitative study was conducted using the conventional content analysis method.Participants and Research ContextData were collected using semi-structured interviews with 19 nurses working in the hospital selected through a purposeful method and analyzed by Graneheim and Lundman approach.Ethical ConsiderationsThe ethics committee of Tehran University of Medical Sciences approved this study with the ethics code IR.TUMS.FNM.REC.1400.187. Informed consent was obtained from all participants. Participants were assured of confidentiality.FindingsFactors influencing professional misconduct by nurses were categorized into three main categories: human factors (nurses’ professional characteristics, personal characteristics of nurses and patient/companion, patient’s clinical condition), procedural factors (procedural conditions, possibility of proving misconduct), and organizational factors (recruitment process, conditions of resources, managing misconduct, bureaucracy, and ward characteristics).ConclusionThis study assists in explaining the factors influencing professional misconduct by nurses. Therefore this study’s results can help managers and planners develop interventions to prevent and correct factors that contribute to misconduct and strengthen factors that prevent misconduct in order to ensure quality and safe patient care.